Risk Factors for Development or Deterioration of Graves' Ophthalmopathy - Stan, Marius N. (Mary Ann Liebert, Inc., 2010)
BACKGROUND: Graves' ophthalmopathy (GO) significantly impairs the quality of life of affected individuals and the most severe cases can be sight threatening. Given the limited therapeutic options, a strong emphasis should be placed on disease prevention to diminish the significant morbidity associated with this disease. SUMMARY: GO is most prevalent in women and most severe in men. Although some genetic differences between GO patients and Graves' disease patients without ophthalmopathy have been identified, none of the polymorphisms identified to date impart a high enough risk of GO to justify genetic testing to guide therapy or preventive strategies. Poorly defined mechanical factors that appear also to play a role in GO susceptibility will likely be better elucidated with advances in imaging techniques. Tobacco smoking has been consistently linked to development or deterioration of GO. Smokers who receive radioactive iodine have the highest incidence of unfavorable GO outcome, which is proportional to the number of cigarettes smoked per day. Several studies have reported an association between radioactive iodine treatment for Graves' disease and worsening or development of GO. Observational studies suggest that the same appears to be true for thyroid dysfunction, including both hyper- and hypothyroidism. While thyrotropin receptor antibody levels appear to be useful in predicting the course of disease and response to therapy, it is not known whether they are predictive of GO development. The puzzling scenarios of euthyroid or clinically unilateral GO, the large number of nonsmoking GO patients, and the occasional development of GO years after thyroid dysfunction has been treated all underline the multifactorial etiology of this disorder in which no single factor determines the clinical outcome. CONCLUSIONS: GO appears to have a complex genetic basis with multiple susceptibility alleles that act in combination with nongenetic factors to contribute to disease expression.